Employee Adaptation To Artificial Intelligence In The Workplace: A Phenomenological Study In South Sulawesi Companies - Dipoatmodjo, Tenri Sayu Puspitaningsih; Burhanuddin; Arif, Hery Maulana (Economics and Business Journal (ECBIS), 2026)
The rapid integration of Artificial Intelligence (AI) into organizational systems has transformed workplace dynamics, employee responsibilities, and patterns of human labor. Although AI implementation improves operational efficiency and productivity, it also creates psychological and professional challenges for employees adapting to technological change. This study aims to explore the lived experiences, emotional responses, and adaptation strategies of employees in South Sulawesi companies undergoing AI-driven digital transformation. This research employed a qualitative phenomenological approach. Data were collected through in-depth semi-structured interviews with 20 participants from the banking, manufacturing, retail, technology, and service sectors in South Sulawesi, Indonesia. Participants were selected using purposive sampling based on direct exposure to AI systems and a minimum of 1.5 years of work experience. The data were analyzed using thematic analysis to identify recurring patterns and meanings related to employee adaptation. The findings revealed six major themes: AI as a tool for improving efficiency and productivity, fear of job displacement and career uncertainty, the importance of continuous learning and digital skill development, the role of organizational support and leadership communication, the emergence of human–AI collaboration, and varied psychological responses to technological change. Employees who received organizational support and training demonstrated greater adaptability and confidence in responding to AI implementation. The study emphasizes the importance of human-centered change management strategies that prioritize psychological safety, transparent communication, and continuous digital training. This research contributes to the limited phenomenological literature on AI adaptation in Indonesia and provides practical implications for human resource management and organizational behavior in the era of digital transformation.